Permeable membrane with COF layer growing on surface as well as preparation method and application of permeable membrane

By growing COF layers on the surface of ECMO membrane materials, the problem of difficult balance between gas permeability and anti-blood leakage properties of existing membrane materials is solved, and efficient gas exchange and good blood compatibility are achieved.

CN119746660AActive Publication Date: 2025-04-04SICHUAN UNIV

Patent Information

Application Number
CN202411897001.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-04-04
Estimated Expiration
2044-12-23

AI Technical Summary

Technical Problem

Existing ECMO membrane oxygenator materials are difficult to balance between gas permeability and anti-blood leakage performance, resulting in a risk of reduced gas exchange efficiency and thrombosis.

Method used

By growing a covalent organic frame (COF) layer on the surface of membrane materials such as polyethersulfone, the enrichment of small pore structures and surface amino groups is used to improve gas permeability and protein adhesion resistance, thereby balancing gas exchange and hemocompatibility.

Benefits of technology

The balance between gas permeability and anti-blood leakage performance in ECMO applications is achieved, the gas exchange efficiency is improved, the risk of thrombosis and immune response is reduced, and the anti-fouling and hemocompatibility of the modified membrane is better than that of the unmodified membrane.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119746660A_ABST
    Figure CN119746660A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of membrane materials, and particularly relates to a permeable membrane with a COF layer growing on the surface and a preparation method and application of the permeable membrane. According to the invention, aldehyde monomers are introduced into a membrane casting solution for blending, and a porous basement membrane with aldehyde groups on the surface is obtained through a phase inversion method; then, the aldehyde group porous substrate membrane is put into an acid reaction solution containing aldehyde monomers and sufficient amine monomers containing guanidine groups in an in-situ growth mode to obtain the porous permeable membrane with the multi-amino COF growing on the surface, the porous substrate guarantees good gas permeability, and the thin and compact surface also guarantees that the membrane does not leak liquid for a long time. In addition, enrichment of amino groups on the surface also promotes affinity of the material to carbon dioxide, and gas exchange in ECMO application is facilitated. In addition, the COF layer grown on the surface also improves the protein adhesion resistance of the porous basement membrane.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of membrane materials, and in particular relates to a permeable membrane with a COF layer grown on the surface, and a preparation method and application thereof. Background Art

[0002] The working principle of extracorporeal membrane oxygenation (ECMO) is to lead the patient's venous blood outside the body, oxygenate it through a membrane oxygenator and remove carbon dioxide, and then lead it back into the patient's body. It uses extracorporeal life support to treat acute respiratory failure, cardiogenic or septic shock, toxic ingestion, thyroid poisoning and other diseases. ECMO is called the "last straw" for patients because it can replace the patient's normal lung function in an emergency. The most core and critical part of ECMO is the membrane oxygenator (MO). As an intermediate medium that is in contact with blood and external oxygen at the same time, the blood compatibility, gas permeability and anti-plasma penetration ability of MO are very important.

[0003] The three materials that have been successfully industrialized are PDMS, PP and PMP. As the first-generation membrane oxygenator material, polydimethylsiloxane (PDMS) has excellent gas permeability. Its oxygen permeability coefficient reaches 600 Barrer, which is much higher than ethyl cellulose (20 barrer) and polyethylene (1-8 Barrer). However, its mechanical strength is low and its thickness needs to be increased by more than 100 microns, which will directly lead to a decrease in gas exchange efficiency. Compared with dense PDMS, porous membrane polypropylene (PP) has low gas transmission resistance, good blood compatibility and non-toxicity, so it was selected as the second-generation oxygenator membrane material. However, its porous structure, which is beneficial to gas transmission, will lead to the risk of plasma leakage on the other hand. In addition to affecting the gas exchange rate, it will also cause complex immune reactions such as thrombosis, so it is not conducive to long-term support of extracorporeal circulation. The third-generation membrane material polymethylpentene (PMP) successfully solved the problem of blood leakage and has good gas permeability. However, in addition to its complex technical bottleneck of film formation, poor blood compatibility is also an important problem that limits its long-term operation. Therefore, a modification strategy is needed to achieve a balance between gas permeability and blood leakage resistance while ensuring good blood compatibility of the membrane oxygenator to meet the needs of ECMO use.

[0004] Covalent organic framework (COF) is a new type of porous crystalline material. Due to its tunable structure and special chemical groups, COF can be endowed with low density, large specific surface area, controllable pore size and the introduction of specific functional sites, which makes it have great prospects and opportunities in the field of membrane separation. At present, the research on COF membranes has covered gas separation membranes, liquid phase separation membranes, proton exchange membranes in fuel cells, etc. Although the application of COF membranes in the field of ECMO has not been widely reported, its characteristics are worthy of further exploration of its application potential in this field. The pore size of porous COF reported so far ranges from 0.5 to 4.7 nanometers. The small pore structure can effectively provide more efficient and abundant gas transmission channels in the case of blood leakage.

[0005] Polyethersulfone (PES) has excellent mechanical properties and good blood compatibility, and is widely used in biomaterials. It has also been tried as an ECMO membrane oxygenator in previous studies. However, its ability to resist protein adhesion is poor. When the membrane oxygenator is used for a long time, the accumulation of proteins in the blood on the membrane can easily affect gas exchange or cause immune reactions such as thrombosis. In addition, the film formation method will also have a great impact on the material structure. The thermally induced phase separation method can obtain a dense PES membrane, which is beneficial for preventing blood leakage while also hindering gas exchange. The non-solvent induced phase separation (NIPS) method can obtain an asymmetric PES membrane with a large porosity that is conducive to gas exchange, but it is difficult to balance its ability to prevent plasma leakage at the same time. Summary of the invention

[0006] In order to solve the above problems, the present invention uses COF with a small pore structure to modify PES through a unique surface growth method, successfully making up for the defects of PES in ECMO applications. Furthermore, the present invention also anticipates that this COF surface growth method can be applied to other permeable membranes suitable for ECMO, such as PDMS, PP and PMP membranes.

[0007] Specifically, in one aspect, the present invention provides a method for preparing a permeable membrane having a COF layer grown on the surface, which comprises the following steps:

[0008] (1) blending a permeable membrane material and an aldehyde monomer to form a membrane to obtain an aldehyde-containing permeable membrane;

[0009] (2) The obtained aldehyde-modified permeable membrane is immersed in an aqueous solution containing an aldehyde monomer, an amine monomer containing a guanidine group, and an acid catalyst, and a permeable membrane with a COF layer grown on the surface is obtained through a Schiff base reaction between the aldehyde group and the amino group.

[0010] Furthermore, the permeable membrane material includes polydimethylsiloxane, polypropylene, polymethylpentene or polyethersulfone.

[0011] Further, the aldehyde monomer includes trialdehyde phloroglucinol, 2,4-dihydroxy-1,3,5-pyromellitic trimaldehyde, 2-hydroxy-1,3,5-benzene trimaldehyde, trimellitic trimaldehyde, terephthalaldehyde, 2,5-dihydroxyterephthalaldehyde, 2-hydroxybenzene-1,4-dicarboxaldehyde, 4,6-diadehydic pyrocatechol, 2,4-diformyl phloroglucinol, 2,4-dihydroxyisophthalaldehyde, 2-hydroxyisophthalaldehyde, 2,6-diformyl-4-methylphenol, or 4-hydroxyisophthalaldehyde. Further, the aldehyde monomer is 2,5-dihydroxyterephthalaldehyde.

[0012] Further, the aldehyde monomers in step (1) and step (2) may be the same or different aldehyde monomers. Further, the aldehyde monomers in step (1) and step (2) are the same aldehyde monomers.

[0013] Further, the amine monomer containing a guanidine group is triaminoguanidine hydrochloride or 1,3-diaminoguanidine hydrochloride. Further, the amine monomer containing a guanidine group is triaminoguanidine hydrochloride.

[0014] Further, the acid catalyst includes hydrochloric acid, sulfuric acid, nitric acid, acetic acid, p-toluenesulfonic acid, scandium trifluoromethanesulfonate or trifluoroformic acid. Further, the acid catalyst is acetic acid with a concentration of 3-6M.

[0015] Furthermore, the film formation after blending in step (1) includes forming the film using any method suitable for forming the permeable membrane material, for example, it may include dissolving the permeable membrane material and the aldehyde monomer in an organic solvent, and preparing the aldehyde-formulated permeable membrane by a phase conversion membrane method.

[0016] Furthermore, the organic solvent includes one or more of N,N-dimethylformamide, N,N-dimethylacetamide, dichloromethane, dimethyl sulfoxide, and N-methylpyrrolidone.

[0017] Furthermore, the phase conversion film method uses a non-solvent induced phase separation method to form a film.

[0018] Furthermore, the phase conversion film forming method comprises the following steps:

[0019] S1: dissolving the permeable membrane material and the aldehyde monomer in an organic solvent, and obtaining a casting solution after degassing;

[0020] S2: Casting the casting liquid of S1 on a substrate, and then immersing the substrate coated with the casting liquid in an anti-solvent coagulation liquid until a film is formed, and after the solvent is removed and dried, a aldehyde-formyl permeable membrane is obtained.

[0021] Furthermore, the substrate includes glass, metal plate or release paper.

[0022] Furthermore, the anti-solvent coagulation liquid can be pure water, ethanol or a mixed solution thereof.

[0023] Furthermore, the film forming temperature is 20-40°C.

[0024] Furthermore, the solvent removal includes soaking the formed membrane in an anti-solvent coagulation liquid for a time sufficient to remove the solvent.

[0025] Furthermore, the Schiff base reaction comprises reacting at 10-100° C. for 1-30 days.

[0026] Furthermore, the ratio of the total molar amount of the aldehyde monomers to the molar amount of the amine monomers containing guanidine groups is 1:0.8-1.2.

[0027] In other aspects, the present invention provides a permeable membrane having a COF layer grown on the surface thereof, which is prepared by the preparation method described herein.

[0028] In other aspects, the present invention also provides use of a permeable membrane having a COF layer grown on the surface as prepared or described herein in extracorporeal membrane oxygenation.

[0029] Further, the permeable membrane having a surface-grown COF layer as prepared or described herein can be used as an ECMO membrane.

[0030] In addition, the permeable membrane having a surface-grown COF layer as prepared or described herein can also be used as an antifouling membrane, a separation membrane, and the like.

[0031] Beneficial effects of the present invention

[0032] The present invention first blends aldehyde monomers with a polymer matrix to prepare a membrane with buried monomers in the matrix, and then puts the aldehyde-modified porous substrate membrane into an acidic reaction solution containing aldehyde monomers and a sufficient amount of amine monomers containing guanidine groups by in-situ growth to obtain a porous permeable membrane with surface growth of polyamino COF. The porous substrate not only ensures good gas permeability, but also the thin dense layer on the surface ensures that the membrane will not leak for a long time. The enrichment of surface amino groups also promotes the affinity of the material for carbon dioxide, which is beneficial to gas exchange in ECMO applications. In addition, the COF layer grown on the surface also improves the anti-protein adhesion performance of the porous substrate membrane. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 The following table shows (A) infrared spectra of the three membrane materials in the embodiments and comparative examples; (B) thermogravimetric curves; (C) X-ray photoelectron spectra; and (D) C1s spectra.

[0034] Figure 2 Scanning electron microscope images of (A) the surface and (B) the cross-section of three membrane materials in Examples and Comparative Examples are shown.

[0035] Figure 3 The dissolution of (A) PES-NH2 in DMAc in the examples and comparative examples is shown; (B) the dissolution of PES-COF in DMAc; (C) infrared characterization of the undissolved surface layer after the PES-COF substrate is dissolved in DMAc and (D) X-ray diffraction.

[0036] Figure 4 (A) The static water contact angles of the four membrane materials are shown; (B) The fluorescence of the four materials was observed by laser confocal microscopy after incubation with FITC-BSA; (C) The fluorescence intensity of the four materials was statistically analyzed by Image-J to evaluate the adhesion of BSA.

[0037] Figure 5 The blood compatibility evaluation results of three membrane materials in Examples and Comparative Examples are shown.

[0038] Figure 6 The test results of blood coagulation time and blood fibrinogen content in the blood and the blood sample control group after incubation with the three materials in the embodiment and the comparative example are shown.

[0039] Figure 7 The gas permeation test results of CO2 and O2 of the three membrane materials in the embodiments and comparative examples are shown.

[0040] Figure 8 The results of gas exchange performance tests on four membrane materials using an ECMO simulation system are shown.

[0041] Fig. 9 The results of the tests and comparisons of the O2 and CO2 exchange performances of PES-COF and PES-CHO membranes are shown.

[0042] Fig.10 Shown are the results of long-term humidity testing on PES-COF.

[0043] Fig.11 A schematic diagram showing the application of the PES-COF of the present invention in ECMO is shown. DETAILED DESCRIPTION

[0044] The present invention takes PES as an example and uses COF with a small pore structure to modify PES. First, the monomer 2,5-dihydroxyterephthalaldehyde (Dha) is introduced into the casting solution for blending, and a porous substrate membrane PES-CHO with aldehyde groups on the surface is obtained by a phase inversion method. Then, the aldehyde-modified PES-CHO is placed in an acidic reaction solution containing Dha and a sufficient amount of triaminoguanidine hydrochloride (TAG·HCl) by in-situ growth to obtain a PES-COF membrane with multi-amino COF grown on the surface. The porous substrate not only ensures good gas permeability, but also the thin dense layer on the surface ensures that the membrane will not leak for a long time. In addition, the enrichment of surface amino groups also promotes the affinity of the material for carbon dioxide, which is beneficial to gas exchange in ECMO applications. After characterizing the structure and surface properties of the material, we tested the anti-adhesion properties of the material to BSA protein by laser confocal microscopy and BCA kit. In addition, the performance of the material in actual application scenarios was verified by gas permeation tests, blood tests and ECMO simulation tests. This study further explored the application potential of the COF structure in the field of ECMO.

[0045] The present invention is further described below in conjunction with specific examples, but the examples do not limit the present invention in any form. The polyethersulfone (PES, Ultrason E6020P) used in the examples was provided by BASF Chemical Company of Germany. 2,5-Dihydroxyterephthalaldehyde (Dha) and triaminoguanidine hydrochloride (TAG·HCl) were purchased from Adamas. Unless otherwise specified, other reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0046] Example 1: Preparation of polyethersulfone with COF layer grown on the surface

[0047] Polyethersulfone (5g, 25wt%) and 2,5-dihydroxyterephthalaldehyde (33.2mg, 0.2mmol) were stirred and dissolved in N,N-dimethylacetamide (DMAc, 15g), and then cast on a clean glass sheet by a homopolymer after degassing in a vacuum oven. The glass sheet coated with the casting solution was immersed in pure water, and the membrane PES-CHO was obtained by liquid-liquid phase conversion. The obtained membrane was immersed in pure water for one week, and then dried and stored for further use.

[0048] Triaminoguanidine hydrochloride (42 mg, 0.3 mmol) and 2,5-dihydroxyterephthalaldehyde (16.6 mg, 0.1 mmol) were dissolved together in 40 mL of 3 M acetic acid solution and ultrasonicated for 20 minutes. The obtained PES-CHO was immersed in the solution and reacted at room temperature for 7 days. The triaminoguanidine hydrochloride monomer was introduced into the membrane surface through the Schiff base reaction and a COF-like structure was formed on the membrane surface to obtain a polyethersulfone material PES-COF with a COF layer grown on the surface.

[0049] Comparative Example 1:

[0050] Polyethersulfone (25wt%) and 2,5-dihydroxyterephthalaldehyde (0.2mmol) were stirred and dissolved in N,N-dimethylacetamide (DMAc), and then degassed in a vacuum oven and cast on a clean glass sheet by a homopolymerizer. The glass sheet coated with the casting solution was immersed in pure water, and the membrane PES-CHO was obtained by liquid-liquid phase conversion. The obtained membrane was immersed in pure water for one week, and then dried and stored for further use.

[0051] Triaminoguanidine hydrochloride (0.2 mmol) was dissolved in 3 M acetic acid solution, ultrasonicated for 20 minutes, and the obtained PES-CHO was immersed in the solution and reacted at room temperature for 7 days. The triaminoguanidine hydrochloride monomer was introduced into the membrane surface through Schiff base reaction to obtain the material PES-NH2.

[0052] Test Example 1: Characterization of membrane materials

[0053] The chemical structures of the different films in the examples and comparative examples were characterized by ATR-FTIR (NICOLET iS50) spectrometer in the range of 400 to 2000 cm -1 . XPS (ESCALAB250XI, Thermo Fisher Scientific) and EDS (OctaneElect Super, EDAX) were used to characterize the elemental composition and chemical state of the membrane surface. Scanning electron microscope (Thermo Fisher Scientific) was used to observe the surface and cross-sectional morphology of the membrane. The thermal stability of the membrane was determined by thermogravimetric curve (TGA, Mettler-Toledo, Switzerland). In addition, the hydrophilicity of the membrane surface was characterized by water contact angle (Theta Lite, Biolin Scientific, Sweden), and the membrane surface roughness was tested by AFM (Icon, Bruker). The results are described below.

[0054] Firstly, the surface groups of the three membrane materials were characterized by Fourier transform infrared absorption spectrometer (FTIR). Figure 1 A. It can be observed at 1640cm -1 The carbonyl peak of PES-CHO was introduced due to the co-blending of Dha, while the carbonyl peak of PES-NH2 disappeared. This is because an excess of triaminoguanidine hydrochloride (TAG·HCl) was added during the post-treatment reaction of PES-CHO, and the Schiff base reaction consumed the aldehyde groups on the membrane surface. During the preparation of the PES-COF material, 2,5-dihydroxyterephthalaldehyde (Dha) and triaminoguanidine hydrochloride were added at the same time. Therefore, the COF-like structure formed on the surface still has unreacted carbonyl groups. The temperature-mass changes of the three membrane materials were also characterized by thermogravimetric analyzer (TGA), such as Figure 1B. It can be seen that PES-CHO has the highest weight loss rate, while PES-COF has the lowest weight loss rate. This is because the specific gravity of PES becomes smaller after modification, and the introduction of new substances on the surface of the material is less likely to degrade at high temperatures. In addition, the surface elements of the material are analyzed by X-ray photoelectron spectroscopy (XPS). Figure 1 C and Table 1 show that the surface N content of PES-NH2 and PES-COF increases due to the introduction of TAG·HCl, and the highest N content in PES-COF is 5.90%. Figure 1 D shows the detailed C1s spectra of the three films. The C1s core-level spectrum has four peaks at binding energies of 284.8 eV, 285.7 eV, 287.9 ​​eV, and 292.0 eV, corresponding to CC, CN(CO), C=O, and CS. The analysis confirms the successful introduction of triaminoguanidine hydrochloride and COF-like structures, respectively.

[0055] Table 1: XPS element content analysis of three membrane materials in the embodiments and comparative examples

[0056]

[0057] Test Example 2: Surface properties of membrane materials

[0058] In order to explore the structural changes on the surface of the membrane material before and after modification, we observed the surface and cross-sectional structure of the material using a scanning electron microscope (SEM). Figure 2 As shown in A, we can see that there is no observable pore structure on the surface of the three membranes, and the surface of the materials is relatively flat before and after modification. Figure 2 As shown in B, after the membrane was broken by liquid nitrogen, the cross-sectional structure was observed and it can be seen that the introduction of 2,5-dihydroxyterephthalaldehyde small molecules into the casting solution increased the porosity to a certain extent during the phase transition process, making the PES-CHO cortex thinner. The modified PES-NH2 and PES-COF both showed a dense layer of about 1.2 microns thick, which was due to the growth of a continuous coating on the surface after the introduction of TAG·HCl and COF-like structures.

[0059] When PES-NH2 and PES-COF are dissolved in DMAc, the substrate PES dissolves quickly, but the coating after the surface reaction is insoluble in DMAc. Since the surface reaction of synthesized PES-NH2 is mainly the Schiff base reaction between Dha buried in the substrate and TAG·HCl in the solution system, the structure is not so complete. Therefore, after the substrate PES is completely dissolved in DMAc, the strength is low and it becomes fragments that are cracked in the solvent, such as Figure 3As shown in A. The surface reaction of synthesized PES-COF is that the Dha buried in the substrate reacts with TAG·HCl, and at the same time, the Dha in the solution system reacts with the free TAG·HCl that has been fixed on the surface to form a COF-like coating on the surface. The structure is continuous and stable. After the substrate PES is dissolved in DMAc, the surface layer remains stable and intact, as shown in Figure 3 As shown in B.

[0060] The COF-like coating obtained after PES-COF dissolution was naturally dried at room temperature and then characterized. It can be seen from the infrared spectrum that ( Figure 3 C), at 3450cm -1 There is a stretching vibration peak of -NH-(-OH) group at 1650cm -1 The presence of the stretching vibration peak of the -C=N- group at , further verified the surface structure. Then, the crystallinity of the material was verified by XPS. Figure 3 D, no crystallization peak was observed. This is because the position of Dha buried in the substrate PES is restricted, which affects the subsequent structure and prevents it from crystallizing in an orderly manner.

[0061] Test Example 3: Antifouling performance test

[0062] Protein fouling is the most critical part of membrane fouling, so the material's anti-protein adhesion performance is a point worthy of attention. Anti-protein adhesion mainly has four molecular-level characteristics: the presence of polar functional groups, the presence of hydrogen bond acceptor groups, the absence of hydrogen bond donor groups, and the absence of net charge. Pure polyethersulfone materials have weak anti-fouling ability and fast protein adhesion. In order to explore the anti-fouling performance of the materials in this study, the three materials were compared with PES. First, the surface hydrophilicity of the four membrane materials was tested. The enhancement of surface polarity improved the hydrophilicity of the materials, such as Figure 4 A. With further reaction, the hydrophilicity gradually increased, and the water contact angle decreased from 86° for PES-CHO to 78° for PES-NH2 and 74° for PES-COF. Next, the anti-protein adhesion performance of the material was tested. After the material was incubated with FITC-BSA under dark conditions for 3 hours, the free fluorescent labeled protein was washed away with PBS buffer. After observation by laser confocal microscopy and statistical fluorescence intensity, we found that compared with pure polyethersulfone membrane, the three membrane materials in this study have very good anti-protein adhesion properties. This is due to the introduction of polar groups such as hydroxyl, aldehyde, and amide structures. Among them, carbonyl and amide structures are hydrogen bond receptor groups, which are more favorable for anti-protein adhesion. This is beneficial to improve the antibacterial properties and blood compatibility of the material to a certain extent ( Figure 4 B and 4C).

[0063] Test Example 4: Blood Compatibility Assessment

[0064] As the medium for the exchange of blood gas and external oxygen in the artificial membrane lung, the membrane material must have good blood compatibility. Here we conducted blood compatibility tests on these three membrane materials. First, we incubated the materials and red blood cells together in a shaking environment at 37 degrees Celsius. After three hours, the EP tube containing the materials and red blood cells was centrifuged. Figure 5 B shows that the supernatants of the EP tubes of the three material samples are all transparent, and there is no obvious hemoglobin release after incubation with red blood cells. At the same time, by testing the absorbance of the supernatant to calculate the hemolysis rate of the material, we can see that the hemolysis rate of all materials is less than 1% ( Figure 5 A), which is significantly lower than the ISO standard (5%). Then, the red blood cells and platelets attached to the surface of the material were fixed with 2.5wt% glutaraldehyde for 24 hours, dehydrated with ethanol gradient, and observed with a scanning electron microscope after drying at room temperature. Figure 5 C. It can be observed that the red blood cells on the surface of PES-COF are in the shape of regular discs with a concave center, while the red blood cells on the surface of PES-NH2 are also disc-shaped, but with irregular edges, while the red blood cells on the surface of PES-CHO are all deformed and present a spike shape. Observation of platelet adhesion revealed that the platelets on the surface of PES-COF were partially deformed, but not obviously activated, while the platelets on the surfaces of PES-CHO and PES-NH2 were obviously activated, with pseudopodia and aggregated adhesion to the surface of the material. The effects of several membranes on blood cells were tested by blood routine tests, such as Figure 5 As shown in Figures D and 5E, the number of red blood cells (RBC), white blood cells (WBCs) and platelets (PLT) in the blood after incubation with PES-COF was not significantly different from that in the control group. The hemoglobin concentration (HGB) and hematocrit (HCT) were not affected by the material, while the blood cell parameters of the other two materials were more or less different from those of the control group. At the same time, the results of the blood flow cytometer also showed that the blood cells treated with PES-COF were consistent with those of the control group ( Figure 5 F).

[0065] In addition, in order to explore the effects of the three materials on the coagulation system, we tested the coagulation time APTT, PT, TT, Fbg and fibrin concentration of plasma after treatment with the three membrane materials and compared them with the control group. Figure 6 As shown, it was found that none of the three materials promoted coagulation, which is beneficial for the use of blood contact materials. Therefore, the blood compatibility characterization results showed that the prepared PES-COF membrane had good blood compatibility and was superior to the other two membranes.

[0066] Test Example 5: CO2 and O2 gas permeation test

[0067] In order to evaluate the gas permeability of the membranes before and after modification, we systematically analyzed the gas permeability of the three membranes using the differential pressure method. Figure 7 As shown in A, compared with the original PES and PES-CHO membranes, the permeability of carbon dioxide and oxygen of PES-NH2 and PES-COF is slightly reduced, but this does not have a substantial impact. The oxygen and carbon dioxide permeabilities (Barrer) of PES-COF reach 83.4 and 219.0, respectively, and with the modification, the CO2 / O2 selectivity of PES-COF is increased to 2.6. The thickening of the dense layer after modification does not significantly affect the permeability of carbon dioxide to the material, which is beneficial to the ECMO system ( Figure 7 B).

[0068] Test Example 6: Gas Permeability Performance in ECMO Simulated Circulation System

[0069] In the clinical application of ECMO, membrane materials are used as intermediate media that are in contact with blood and oxygen at the same time, and they play the role of promoting blood oxygenation and carbon dioxide removal. Therefore, they need to have good gas exchange capacity and liquid barrier properties. Therefore, we built our own ECMO simulation system and tested several membrane materials (such as Figure 8 A). The membrane is fixed between the two chambers. Saturated carbon dioxide water is added to the flask and maintained at 37 degrees Celsius. The solution is circulated in the upper chamber by a pump. The concentrations of carbon dioxide and oxygen in the solution are tested by related instruments. One end of the lower chamber is connected to an oxygen cylinder to control the oxygen flow rate, and the other end can be used to test the environmental humidity by related instruments.

[0070] We used this simulated circulation device to test the gas exchange performance of four membrane materials. Through the experimental results, we found that Figure 8 B. Compared with PES-CHO, the modified PES-NH2 and PES-COF can promote the passage of oxygen and carbon dioxide. After 30 minutes, the carbon dioxide content in the solution decreased to 51.2%, 43.4%, and 44.4% of the original, respectively, and the liquid oxygen concentration increased from 0.76ppm to 4.48, 5.76, and 4.83, respectively. The change in carbon dioxide concentration in the gas phase also shows that the rate of increase of PES-NH2 and PES-COF has significantly accelerated. It can be seen that under the ECMO simulation system, the gas permeability of PES-NH2 and PES-COF is significantly superior to that in a simple gas phase environment. This may be because in the absence of pressure, compared with the obstruction caused by the increase in the thickness of the surface dense layer, the polarity of the material surface plays a greater role in promoting gas permeation.

[0071] Although PES-NH2 has the best gas exchange performance in the ECMO simulation system, comprehensive blood compatibility evaluation shows that PES-COF is the best candidate for artificial membrane lung, and its gas permeability has exceeded most of the polymer membranes studied. Therefore, in order to evaluate the actual oxygenation and carbon dioxide removal performance, the saturated carbon dioxide water in the upper chamber was replaced by pig blood, and the O2 and CO2 exchange performance of the membrane was evaluated using a blood gas analyzer while maintaining the ambient temperature at 37°C and the blood-gas ratio at 1:2.5. Fig. 9 As shown in the figure, the test shows that PES-COF can reach blood oxygen saturation (95%) faster than PES-CHO, and the CO2 elimination rate is also faster. The gas fluxes of O2 and CO2 are 103.70 ml / (min·m 2 ) and 755.95ml / (min·m 2 ), the area of ​​the ECMO membrane lung is usually 1 to 3 m 2 , which can meet the gas exchange efficiency of ECMO used clinically (250 ml / min). At the same time, after blood circulation, the surface of PES-COF did not change significantly.

[0072] In addition to gas permeability, plasma leakage is also a key issue for membrane oxygenators. During ECMO circulation, plasma may leak through the membrane pores, resulting in decreased gas exchange efficiency and the need to replace the oxygenator. Therefore, we conducted a long-term humidity test on PES-COF, detecting the humidity and temperature changes in the lower chamber under a continuous 120h cycle. Fig.10 As shown in the figure, the relative humidity and temperature fluctuated slightly but did not change significantly, which verified the excellent liquid permeation resistance of the PES-COF membrane. These data confirm that PES-COF has excellent performance and can be used in ECMO systems.

[0073] In summary, in the present invention, a relatively dense COF layer was introduced into the PES surface using an in situ growth strategy to prepare a membrane lung material for ECMO. We introduced Dha monomer into the polyethersulfone casting solution to prepare a aldehyde-modified polyethersulfone membrane, and then introduced the COF layer by co-reacting Dha and TAG·HCl with the aldehyde-modified polyethersulfone membrane. Thanks to the affinity of the surface nitrogen-rich amide groups and unreacted amino groups for carbon dioxide, the modified membrane exhibited significantly enhanced carbon dioxide selectivity. In addition, compared with the original PES membrane, the modified membrane not only has enhanced anti-protein adhesion ability, but also improved blood compatibility. In addition, ECMO simulation tests have shown that the modified membrane exhibits excellent gas exchange performance and anti-leakage. The surface modification method in this study is effective, easy to industrialize, and is also suitable for hollow fiber membranes, which have great application potential.

[0074] It should be noted that the preferred embodiments of the present invention are given in the specification and drawings of the present invention. However, the present invention can be implemented in many different forms and is not limited to the embodiments described in this specification. These embodiments are not used as additional limitations on the content of the present invention. The purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive. In addition, the above-mentioned technical features continue to be combined with each other to form various embodiments not listed above, which are all regarded as the scope of the present invention; further, for ordinary technicians in this field, they can be improved or transformed according to the above description, and all these improvements and transformations should belong to the protection scope of the claims attached to the present invention.

Claims

1. A method for preparing a permeable membrane with a COF layer grown on the surface, characterized in that: The following steps are involved: (1) blending a permeable membrane material and an aldehyde monomer to form a membrane to obtain an aldehyde-containing permeable membrane; (2) The obtained aldehyde-modified permeable membrane is immersed in an aqueous solution containing an aldehyde monomer, an amine monomer containing a guanidine group, and an acid catalyst, and a permeable membrane with a COF layer grown on the surface is obtained through a Schiff base reaction between the aldehyde group and the amino group.

2. The preparation method according to claim 1, characterized in that: The permeable membrane material includes polydimethylsiloxane, polypropylene, polymethylpentene or polyethersulfone.

3. The preparation method according to claim 1, characterized in that: The aldehyde monomers include trialdehyde pyrogallol, 2,4-dihydroxy-1,3,5-pyromellitic trimaldehyde, 2-hydroxy-1,3,5-benzene trimaldehyde, trimellitic trimaldehyde, terephthalaldehyde, 2,5-dihydroxyterephthalaldehyde, 2-hydroxybenzene-1,4-dicarboxaldehyde, 4,6-diadehydic pyrogallol, 2,4-diformyl pyrogallol, 2,4-dihydroxyisophthalaldehyde, 2-hydroxyisophthalaldehyde, 2,6-diformyl-4-methylphenol, or 4-hydroxyisophthalaldehyde; Furthermore, the aldehyde monomers in step (1) and step (2) may be the same or different aldehyde monomers.

4. The preparation method according to claim 1, characterized in that: The amine monomer containing a guanidine group is triaminoguanidine hydrochloride or 1,3-diaminoguanidine hydrochloride.

5. The preparation method according to claim 1, characterized in that: The acid catalyst includes hydrochloric acid, sulfuric acid, nitric acid, acetic acid, p-toluenesulfonic acid, scandium trifluoromethanesulfonate or trifluoroformic acid.

6. The preparation method according to claim 1, characterized in that: The film formation after blending in step (1) comprises dissolving the permeable membrane material and the aldehyde monomer in an organic solvent, and preparing the aldehyde-modified permeable membrane by a phase conversion membrane method.

7. The preparation method according to claim 6, characterized in that: The organic solvent includes one or more of N,N-dimethylformamide, N,N-dimethylacetamide, dichloromethane, dimethyl sulfoxide, and N-methylpyrrolidone; Furthermore, the phase conversion film method uses a non-solvent induced phase separation method to form a film; Furthermore, the phase conversion film forming method comprises the following steps: S1: dissolving the permeable membrane material and the aldehyde monomer in an organic solvent, and obtaining a casting solution after degassing; S2: Casting the casting liquid of S1 on a substrate, and then immersing the substrate coated with the casting liquid in an anti-solvent coagulation bath until a film is formed, and obtaining a aldehyde-modified permeable membrane after solvent removal and drying.

8. The preparation method according to claim 1, characterized in that: The Schiff base reaction comprises reacting at 10-100° C. for 1-30 days; Furthermore, the ratio of the total molar amount of the aldehyde monomers to the molar amount of the amine monomers containing guanidine groups is 1:0.8-1.

2.

9. A permeable membrane with a COF layer grown on the surface, prepared by the preparation method according to any one of claims 1 to 8.

10. Use of a permeable membrane having a surface-grown COF layer prepared by the preparation method according to claim 9 or any one of claims 1 to 8 in extracorporeal membrane oxygenation.

Citation Information

Patent Citations

  • Preparation method of graft-modified covalent organic framework composite membrane pore channel and filter membrane of graft-modified covalent organic framework composite membrane pore channel

    CN114307671A

  • Preparation and application methods of high-permeability selective ion separation membrane

    CN115501763A

  • Preparation method of functionalized covalent organic framework membrane, structure regulation and control method and application of functionalized covalent organic framework membrane in gas separation

    CN118751092A

  • Microwave-assisted method for preparing covalent organic framework nanofiltration membrane and nanofiltration membrane

    CN118987971A

Cited By

  • Preparation method of strong interlayer bonding nanofiltration membrane constructed by solid-liquid interfacial polymerization and product and application thereof

    CN121775689A

  • Rapid large-size COF film and preparation method and application thereof

    CN122445036A